WEB SERVICE DENGAN METODE REPRESENTATIONAL STATE TRANSFER (REST) UNTUK SMART CAMPUS UNISBANK DENGAN FRAMWORK CODEIGNITER - Rezal Arminto, Edo; Zuliarso, Eri (Information Technology and Telematics, 2018)
ABSTRACT University of Stikubank started On April 28, 1968 from July 5, 2001, officially STMIK, STIBA and STIH Stikubank has changed shape and joined UNIVERSITAS STIKUBANK Semarang, the advancement of technology in the field of web and android very fast then smart campus which is only mobile web in develop the author to be Smart campus based on android. Data collection method used is observation method, interview and literature study. Methodology of system development in this research use Prototype methodology. The result of this research is creating smart campus application based on android, and in its management research using Codeigniter Framework with Representational Transfer method so that applicator is easy to take student data and safe from hacker.